Framing the Discourse on Gender and Corruption - Krambia-Kapardis, Maria; Williams, Sope; Kihl, Lisa (My University, 2025)
Corruption is a global problem that has hindered socioeconomic development and exacerbated inequality and instability around the world (Lawder, 2016; Chayes, 2016). The United Nations (UN) has described corruption as “an insidious plague that has a wide range of corrosive effects on societies” (United Nations [UN], 2004, p. iii). Corruption undermines democracy and the rule of law, leads to violations of human rights, erodes citizens’ quality of life, and enables organized crime, terrorism, and other threats to human security to flourish (UN, 2004).
Keywords: gender; corruption